Nucleotide sequence variants, gene expression and serum profile of immune and antioxidant markers associated with brucellosis resistance/susceptibility in Shami goat - Ahmed A. Elsayed; Ahmed M. Sallam (Irish Veterinary Journal)
Abstract Brucellosis is a highly contagious zoonotic bacterial disease. It has considerable negative consequences on the animal production industry worldwide. The objective of this study was to investigate the genetic and molecular variations in Shami goat susceptible to Brucella infection. Blood samples were collected from fifty mature Shami goats (30 Brucella-infected does and 20 non-infection). DNA was extracted and selected parts the immunity; solute carrier family 11 member 1 (SLC11A1), toll-like receptor 1 (TLR1), toll-like receptor 9 (TLR9), SP110 nuclear body protein (SP110), the adenosine A3 receptor (ADORA3), caspase activating recruitment domain 15 (CARD15) and interferon regulatory factor 3 (IRF3), antioxidant glutathione peroxidase 1 (GPX1), nitric oxide synthase (NOS), NAD(P)H dehydrogenase [quinone] 1 (NQO1) and transcription factor NF-E2-related factor 2 (Nrf2) and erythritol related transketolase (TKT), ribose 5-phosphate isomerase (RPIA) and Adenosine monophosphate deaminase (AMPD) genes were sequenced. Likewise, the levels of gene expressions were investigated. The results identified polymorphic variants between healthy and infected does. Levels of gene expression of SLC11A1, TLR1, TLR9, SP110, ADORA3, CARD15, IRF3, HMOX1, TKT, RPIA and AMPD were significantly (P < 0.05) up regulated in the infected compared to the non-infected ones. On the other hand, GPX1, NOS, NQO1 and Nrf2 genes were significantly (P < 0.05) downregulated in the infected compared to the non-infected does. The results of serum profile indicated that there is a significant (P < 0.05) increase in the activities of AST, ALT, GGT, LDH, ALP as well as serum level of globulin, triglycerides, cholesterol, MDA, NO, IL-1β, TNF-α, IgM, IgG, haptoglobin and amyloid A. On the other hand, there were significant reductions in the glucose, total protein albumin, urea, calcium, inorganic phosphorus, sodium, copper, zinc, iron, TAC, GSH, SOD, GPx, IL-10 and fibrinogen in the infected compared to the non-infected does. Our results provide valuable information about the serum profile variations and putative genetic markers for Brucella infection in goats. This could be utilized in controlling goat brucellosis through selective breeding of natural resistant animals.